ANALYSIS OF HUMAN BODY STRUCTURE (Scientific journal of the Fergana State University, 2023)
This article aims to analyze the study of human body mass by various methods and to identify the most effective method. There are a number of research methods in this area, which are used in our daily lives, medicine, sports and various other fields. Several formulas are used to theoretically determine the mass of the human body, and not all of them can accurately determine the composition of the human body. Determining the most effective methods by analyzing the methods and techniques of studying the composition of the human body is one of the main issues on the agenda. We used classical mathematical methods. In our experiments and observations, we measured the height, weight, sitting height, and body fat of young people using clipometry. Due to the large number of issues and questions to consider in our work, we have learned that the formulas adopted in some literature are closer to our experiments. The study found that the students who underwent the experiment had significant deficiencies in their body weight patterns. For example, both interns are healthy. But it is clear that there is a difference in their body composition. In conclusion, many researchers around the world are currently working to find easier ways to do this. Most importantly, we have the task of studying the above parts of the body in order to know the exact weight of a person without determining the fat, bone, muscle mass, water content, and mass of the internal organs.